Review of the genus Sessiluncus (Acari: Mesostigmata: Ologamasidae), description of male and redescription of female of Sessiluncus aegypticus, and notes on some morphological characters of the genus - Kazemi, Shahrooz; Nasr, Abdelrady Korashy; Ramadan, Mahmoud Mohamed; Klompen, Hans (Zootaxa, 2021)
The concept of the genus Sessiluncus G. Canestrini is reviewed, based on a review of the literature and examination of some described and undescribed species. An updated diagnosis of the genus is presented. Valid species of Sessiluncus and their most diagnostic morphological characters are listed. The male of S. aegypticus Nasr & Afifi, 1986 is described for the first time based on specimens collected in Egypt, and the female is redescribed from specimens collected in Egypt and Iran. Sessiluncus oculatus Vitzthum, 1935 is reported from Panama, and supplementary information on S. hungaricus Karg, 1964 and S. oculatus is presented. The labrum, paralabrum and paralabral stylus of S. aegpticus are also described. The idiosomal adenotaxy and poroidotaxy of the genus are described and discussed.